Lowest-Low Fertility in South Korea: Policy and Domestic Labor Supports and the Transition to Second Birth. (30th April 2020) - Kim, Joeun; Luke, Nancy
Abstract: Scholars and policymakers contend that severe work-family constraints for women are a key contributor to lowest-low fertility in industrialized countries. Two separate areas of research have examined supports that could alleviate these constraints and potentially increase fertility: institutional support in the form of public policies and domestic labor support from male partners. There are few studies considering the influence of both policy and domestic labor supports and no investigations of the interplay between these two support mechanisms. We develop and test a theoretical framework that considers how the combination of these supports could alleviate women's work-family constraints and increase fertility. Using the case of South Korea, a country with one of the most sustained lowest-low fertility rates in history, we examined the relationship between women's eligibility for parental leave and husbands' share of domestic labor and the transition to a second birth. Our analyses revealed that both supports, independently, had positive effects on the likelihood of a second birth. More importantly, we found that husbands' domestic labor had a positive influence on fertility only when women's access to parental leave was limited, suggesting that policy and domestic labor supports are substitutes and alleviate the same underlying work-family constraint in the Korean context. Our study underscores the importance of understanding the nature of work-family conflict across countries and how various supports―alone or in combination―could relieve women's constraints on childbearing and upturn lowest-low fertility.